Preparation method of sodium ferric sulfate positive electrode material

In the preparation process of sodium ferrous sulfate positive electrode material, ball milling and step-by-step sintering treatment is performed using anhydrous ferrous sulfate, sodium source, carbon source and sintering additives, the problem of poor conductivity of the material is solved, and high discharge specific capacity and good cycle stability are achieved.

CN119551733APending Publication Date: 2025-03-04LEPU SODIUM ELECTRIC NEW MATERIALS (LUAN) CO LTD
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411732154.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-29
Publication Date
2025-03-04

AI Technical Summary

Technical Problem

The existing sodium ferrosulfate positive electrode materials have poor conductivity, resulting in low discharge capacity and low crystallinity, which affects the electrochemical performance of the material.

Method used

A mixture of anhydrous ferrous sulfate, sodium, carbon source and sintering additive is used to perform ball milling and step-by-step sintering treatment under a nitrogen-protected atmosphere to ensure uniform mixing and efficient sintering of raw materials.

Benefits of technology

The conductivity and discharge specific capacity of the sodium ferric sulfate cathode material are improved, the crystallinity and electrochemical properties of the material are enhanced, and the circulation stability of the material is significantly improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119551733A_ABST
    Figure CN119551733A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of sodium ion batteries, in particular to a sodium ferric sulfate positive electrode material. The invention relates to a preparation method of a sodium ferric sulfate positive electrode material. The preparation method comprises the following steps: (1) weighing anhydrous ferrous sulfate, a sodium source, a carbon source and a sintering aid; (2) adding oleic acid, carrying out ball milling in a ball milling tank in a nitrogen protective atmosphere according to a certain ball-to-material ratio, and drying the ball-milled slurry in a vacuum drying oven; and (3) carrying out stepped sintering treatment on the dried sample in a protective atmosphere to obtain the sodium ferric sulfate positive electrode material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of sodium ion batteries, and in particular to a method for preparing a sodium iron sulfate positive electrode material. Technical Background

[0002] At present, developing battery materials with high energy density, long cycle life, abundant resources and low price has become an important challenge facing the world. The working principle of sodium-ion batteries is similar to that of lithium-ion batteries. Its production process can be used for the production of sodium electricity with a slight modification. At present, sodium battery positive electrode materials include three categories: layered oxides, polyanions and Prussian blue. Layered oxides have the characteristics of periodic layered structure, simple preparation, high specific capacity and voltage, but most layered materials are easy to absorb water and react with air, which has a great impact on the stability and electrochemical properties of the materials, so they cannot be stored in the air for a long time. Polyanions include phosphates, fluorinated phosphates, pyrophosphates and sulfates. Since most polyanion positive electrode materials have an open three-dimensional skeleton, they have good rate performance and good cycle performance, but the conductivity of this type of material is generally poor, so when preparing this type of material, it is generally necessary to add conductive materials to increase its conductivity. Prussian blue materials are new positive electrode materials with great development potential in recent years. They have open three-dimensional channels, Na + It can move quickly in the channel, so it has good structural stability and rate performance. Since Prussian blue materials have problems such as difficulty in removing crystalline water, few people on the market have conducted research on such materials.

[0003] As a typical sodium positive electrode material, sodium iron sulfate material has the advantages of high average voltage, low raw material cost, and good safety. However, its conductivity is poor. In order to improve the conductivity of the positive electrode material, non-in-situ carbon conductive agents such as conductive carbon are generally added in the precursor mixing stage. Since these carbon material conductive agents are light and are all nanoparticles, it is difficult to mix them evenly during the mixing process, resulting in the surface of the sodium iron sulfate positive electrode material particles cannot be effectively coated by the carbon source. The discharge specific capacity of the sodium iron sulfate positive electrode material prepared by this method is still very low. In addition, due to low-temperature sintering, there is not enough energy in the sintering process, resulting in low crystallinity of sodium iron sulfate and low reaction efficiency. Summary of the invention

[0004] Therefore, the problem to be overcome by the present invention is to ensure that the raw materials are mixed evenly and to improve the discharge specific capacity and reaction efficiency of the material, thereby providing a method for preparing a sodium iron sulfate positive electrode material that solves the above-mentioned problems.

[0005] The technical solution provided by the present invention is as follows:

[0006] A method for preparing a sodium iron sulfate positive electrode material comprises the following steps:

[0007] (1) Weigh anhydrous ferrous sulfate, a sodium source, a carbon source and a sintering aid;

[0008] (2) adding oleic acid, ball milling in a ball mill under a nitrogen atmosphere according to a certain ball-to-material ratio, and drying the milled slurry in a vacuum drying oven;

[0009] (3) The dried sample is subjected to a step-wise sintering treatment under a protective atmosphere to obtain a sodium iron sulfate positive electrode material.

[0010] The sodium source in step (1) includes one or more of sodium sulfate, sodium bisulfate, sodium carbonate, sodium bicarbonate, sodium oxalate and sodium acetate.

[0011] The carbon source in step (1) includes one or more of carbon nanotubes, ascorbic acid, citric acid, carbon black, graphite, nanographite, graphene and carbon fiber.

[0012] The sintering aid in step (1) includes H 3 BO 3 , B 2 O 3 Or other boron-containing low melting point glass powder.

[0013] The ball-to-material ratio in step (2) is 10-15:1, the ball milling speed is 300-600 r / min, and the ball milling time is 4-6 h.

[0014] The temperature of the vacuum drying oven in step (2) is 80-100° C. and the drying time is 8-12 hours.

[0015] The protective gas in step (3) is nitrogen or argon, the first step sintering temperature is 120-200°C, the insulation time is 3-6h, the second step sintering temperature is 300-400°C, the heating rate is 2-5°C / min, and the insulation time is 8-12h.

[0016] The present invention first adds a sintering aid to anhydrous ferrous sulfate and sodium sulfate in a conventional mixing process to promote a solid phase reaction process during low-temperature sintering. Then, a surfactant is added during the ball milling mixing process of sodium ferrous sulfate to ensure that the raw materials and the carbon source can be evenly mixed. BRIEF DESCRIPTION OF THE DRAWINGS

[0017] Figure 1 A scanning electron microscope (SEM) image of the sodium iron sulfate positive electrode material provided in Example 6 of the present invention;

[0018] Figure 2 A scanning electron microscope (SEM) image of the sodium iron sulfate positive electrode material provided in Comparative Example 2 of the present invention;

[0019] Figure 3 This is a scanning electron microscope (SEM) image of the sodium iron sulfate positive electrode material provided in Comparative Example 4 of the present invention. DETAILED DESCRIPTION

[0020] The positive electrode material and the preparation method thereof of the present invention are further described in detail below with reference to some specific examples.

[0021] Example 1

[0022] Weigh 30.4 g of anhydrous FeSO 4 , 14.2 g Na 2 SO 4 , 2.3474 g of carbon nanotubes and 0.14 g of H 3 BO 3 , add 5 mL of oleic acid, and ball mill the mixture in an inert protective atmosphere at a ratio of ball to material of 15:1. The ball mill speed is set to 400 r / min and the ball milling time is 6 h.

[0023] After ball milling, the sample was placed in a vacuum drying oven at 80°C for 12 h. After the sample was dried, it was ground into powder using an agate mortar and passed through a 400-mesh sieve to obtain a precursor powder.

[0024] The precursor powder was placed in a crucible, heated to 150°C at a heating rate of 2°C / min in a nitrogen atmosphere, kept warm for 6 hours, and sintered for the first time. The temperature was then raised to 350°C at a heating rate of 2°C / min and kept warm for 15 hours to obtain a sodium iron sulfate positive electrode material.

[0025] Example 2

[0026] Weigh 30.4 g of anhydrous FeSO 4 , 14.2 g Na 2 SO 4 , 2.3474 g of carbon nanotubes and 0.14 g of H 3 BO 3 , add 5 mL of oleic acid, and ball mill the mixture in an inert protective atmosphere at a ratio of ball to material of 15:1. The ball mill speed is set to 400 r / min and the ball milling time is 6 h.

[0027] After ball milling, the sample was placed in a vacuum drying oven at 80°C for 12 h. After the sample was dried, it was ground into powder using an agate mortar and passed through a 400-mesh sieve to obtain a precursor powder.

[0028] The precursor powder was placed in a crucible, heated to 150°C at a heating rate of 2°C / min in a nitrogen atmosphere, kept warm for 6 hours, and sintered for the first time. The temperature was then raised to 350°C at a heating rate of 2°C / min and kept warm for 15 hours to obtain a sodium iron sulfate positive electrode material.

[0029] Example 3

[0030] Weigh 30.4 g of anhydrous FeSO 4 , 14.2 g Na 2 SO 4 , 2.3474 g of carbon nanotubes and 0.14 g of H 3 BO 3 , add 5 mL of oleic acid, and ball mill the mixture in an inert protective atmosphere at a ratio of ball to material of 15:1. The ball mill speed is set to 400 r / min and the ball milling time is 6 h.

[0031] After ball milling, the sample was placed in a vacuum drying oven at 80°C for 12 h. After the sample was dried, it was ground into powder using an agate mortar and passed through a 400-mesh sieve to obtain a precursor powder.

[0032] The precursor powder was placed in a crucible, heated to 150°C at a heating rate of 2°C / min in a nitrogen atmosphere, kept warm for 6 hours, and sintered for the first time. The temperature was then raised to 350°C at a heating rate of 2°C / min and kept warm for 15 hours to obtain a sodium iron sulfate positive electrode material.

[0033] Example 4

[0034] Weigh 53.92g of anhydrous FeSO 4 , 34.8 g Na 2 SO 4 , 4.67 g of carbon nanotubes and 0.28 g of H 3 BO 3 , add 7 mL of oleic acid, and ball mill the mixture in an inert protective atmosphere at a ratio of ball to material of 15:1. The ball mill speed is set to 400 r / min and the ball milling time is 6 h.

[0035] After ball milling, the sample was placed in a vacuum drying oven at 80°C for 12 h. After the sample was dried, it was ground into powder using an agate mortar and passed through a 400-mesh sieve to obtain a precursor powder.

[0036] The precursor powder was placed in a crucible, heated to 150°C at a heating rate of 2°C / min in a nitrogen atmosphere, kept warm for 6 hours, and sintered for the first time. The temperature was then raised to 350°C at a heating rate of 2°C / min and kept warm for 15 hours to obtain a sodium iron sulfate positive electrode material.

[0037] Example 5

[0038] Weigh 53.92g of anhydrous FeSO 4 , 34.8 g Na 2 SO 4 , 4.67 g of carbon nanotubes and 0.28 g of H 3 BO 3, add 7 mL of oleic acid, and ball mill the mixture in an inert protective atmosphere at a ratio of ball to material of 15:1. The ball mill speed is set to 400 r / min and the ball milling time is 6 h.

[0039] After ball milling, the sample was placed in a vacuum drying oven at 80°C for 12 h. After the sample was dried, it was ground into powder using an agate mortar and passed through a 400-mesh sieve to obtain a precursor powder.

[0040] The precursor powder was placed in a crucible, heated to 150°C at a heating rate of 2°C / min in a nitrogen atmosphere, kept warm for 6 hours, and sintered for the first time. The temperature was then raised to 350°C at a heating rate of 2°C / min and kept warm for 15 hours to obtain a sodium iron sulfate positive electrode material.

[0041] Example 6

[0042] Weigh 53.92g of anhydrous FeSO 4 , 34.8 g Na 2 SO 4 , 4.67 g of carbon nanotubes and 0.28 g of H 3 BO 3 , add 7 mL of oleic acid, and ball mill the mixture in an inert protective atmosphere at a ratio of ball to material of 15:1. The ball mill speed is set to 400 r / min and the ball milling time is 6 h.

[0043] After ball milling, the sample was placed in a vacuum drying oven at 80°C for 12 h. After the sample was dried, it was ground into powder using an agate mortar and passed through a 400-mesh sieve to obtain a precursor powder.

[0044] The precursor powder was placed in a crucible, heated to 150°C at a heating rate of 2°C / min in a nitrogen atmosphere, kept warm for 6 hours, and sintered for the first time. The temperature was then raised to 350°C at a heating rate of 2°C / min and kept warm for 15 hours to obtain a sodium iron sulfate positive electrode material.

[0045] Example 7

[0046] Weigh 42.6 g of anhydrous FeSO 4 , 85g Na 2 SO 4 , 6.7158 g of carbon nanotubes and 0.40 g of H 3 BO 3 , add 10 mL of oleic acid, and ball mill the mixture in an inert protective atmosphere at a ratio of ball to material of 15:1. The ball mill speed is set to 400 r / min and the ball milling time is 6 h.

[0047] After ball milling, the sample was placed in a vacuum drying oven at 80°C for 12 h. After the sample was dried, it was ground into powder using an agate mortar and passed through a 400-mesh sieve to obtain a precursor powder.

[0048] The precursor powder was placed in a crucible, heated to 150°C at a heating rate of 2°C / min in a nitrogen atmosphere, kept warm for 6 hours, and sintered for the first time. The temperature was then raised to 350°C at a heating rate of 2°C / min and kept warm for 15 hours to obtain a sodium iron sulfate positive electrode material.

[0049] Example 8

[0050] Weigh 42.6 g of anhydrous FeSO 4 , 85g Na 2 SO 4 , 6.7158 g of carbon nanotubes and 0.40 g of H 3 BO 3 , add 10 mL of oleic acid, and ball mill the mixture in an inert protective atmosphere at a ratio of ball to material of 15:1. The ball mill speed is set to 400 r / min and the ball milling time is 6 h.

[0051] After ball milling, the sample was placed in a vacuum drying oven at 80°C for 12 h. After the sample was dried, it was ground into powder using an agate mortar and passed through a 400-mesh sieve to obtain a precursor powder.

[0052] The precursor powder was placed in a crucible, heated to 150°C at a heating rate of 2°C / min in a nitrogen atmosphere, kept warm for 6 hours, and sintered for the first time. The temperature was then raised to 350°C at a heating rate of 2°C / min and kept warm for 15 hours to obtain a sodium iron sulfate positive electrode material.

[0053] Example 9

[0054] Weigh 42.6 g of anhydrous FeSO 4 , 85g Na 2 SO 4 , 6.7158 g of carbon nanotubes and 0.40 g of H 3 BO 3 , add 7 mL of oleic acid, and ball mill the mixture in an inert protective atmosphere at a ratio of ball to material of 15:1. The ball mill speed is set to 400 r / min and the ball milling time is 6 h.

[0055] After ball milling, the sample was placed in a vacuum drying oven at 80°C for 12 h. After the sample was dried, it was ground into powder using an agate mortar and passed through a 400-mesh sieve to obtain a precursor powder.

[0056] The precursor powder was placed in a crucible, heated to 150°C at a heating rate of 2°C / min in a nitrogen atmosphere, kept warm for 6 hours, and sintered for the first time. The temperature was then raised to 350°C at a heating rate of 2°C / min and kept warm for 15 hours to obtain a sodium iron sulfate positive electrode material.

[0057] Comparative Example 1

[0058] Weigh 53.92g of anhydrous FeSO 4 , 34.8 g Na 2 SO 4 , 4.67 g of carbon nanotubes and 0.28 g of H 3 BO 3 The materials were mixed by ball milling in an inert protective atmosphere at a ratio of 15:1 between ball and material. The ball milling speed was set at 400 r / min and the ball milling time was 6 h.

[0059] After ball milling, the sample was placed on a 400-mesh sieve to obtain a precursor powder.

[0060] The precursor powder was placed in a crucible, heated to 150°C at a heating rate of 2°C / min in a nitrogen atmosphere, kept warm for 6 hours, and sintered for the first time. The temperature was then raised to 350°C at a heating rate of 2°C / min and kept warm for 15 hours to obtain a sodium iron sulfate positive electrode material.

[0061] Comparative Example 2

[0062] Weigh 42.6 g of anhydrous FeSO 4 , 85g Na 2 SO 4 , 6.7158 g of carbon nanotubes and 0.40 g of H 3 BO 3 The materials were mixed by ball milling in an inert protective atmosphere at a ratio of 15:1 between ball and material. The ball milling speed was set at 400 r / min and the ball milling time was 6 h.

[0063] After ball milling, the sample was passed through a 400-mesh sieve to obtain a precursor powder.

[0064] The precursor powder was placed in a crucible, heated to 150°C at a heating rate of 2°C / min in a nitrogen atmosphere, kept warm for 6 hours, and sintered for the first time. The temperature was then raised to 350°C at a heating rate of 2°C / min and kept warm for 15 hours to obtain a sodium iron sulfate positive electrode material.

[0065] Comparative Example 3

[0066] Weigh 30.4 g of anhydrous FeSO 4 , 28.4 g Na 2 SO 4 , 3g of carbon nanotubes were mixed by ball milling in an inert protective atmosphere at a ratio of ball to material of 15:1. The ball milling speed was set at 400r / min and the ball milling time was 6h.

[0067] After ball milling, the sample was placed on a 400-mesh sieve to obtain a precursor powder.

[0068] The precursor powder was placed in a crucible, heated to 150°C at a heating rate of 2°C / min in a nitrogen atmosphere, kept warm for 6 hours, and sintered for the first time. The temperature was then raised to 350°C at a heating rate of 2°C / min and kept warm for 15 hours to obtain a sodium iron sulfate positive electrode material.

[0069] Comparative Example 4

[0070] Weigh 53.92g of anhydrous FeSO 4 , 34.8 g Na 2 SO 4 and 4.67 g of carbon nanotubes were ball-milled in an inert protective atmosphere at a ratio of 15:1. The ball-milling speed was set at 400 r / min and the ball-milling time was 6 h.

[0071] After ball milling, the sample was sieved through a 400-mesh sieve to obtain a precursor powder.

[0072] The precursor powder was placed in a crucible, heated to 150°C at a heating rate of 2°C / min in a nitrogen atmosphere, kept warm for 6 hours, and sintered for the first time. The temperature was then raised to 350°C at a heating rate of 2°C / min and kept warm for 15 hours to obtain a sodium iron sulfate positive electrode material.

[0073] The positive electrode materials obtained in each embodiment and comparative example are assembled into button batteries. The specific operation steps are as follows: the positive electrode material, acetylene black and binder polyvinylidene fluoride (PVDF) are mixed in a mass ratio of 8:1:1, and then an appropriate amount of N-methylpyrrolidone (NMP) solution is added to degas to form a slurry. The slurry is evenly coated on the aluminum foil current collector, dried in a vacuum drying oven, and cut into 12mm pole pieces as the battery positive electrode after rolling. Assembled into button batteries in a glove box, in which the sodium sheet is used as the negative electrode, the glass fiber is used as the diaphragm, and the electrolyte is 1mol / LNaClO 4 in EC:PC=1:1Vol%with 5%FEC, the assembled button cells were placed in the Xinwei battery testing system for charge and discharge tests.

[0074] Parameter setting: voltage range 2-4.3V, charge and discharge at 0.1C / 0.1C for the first three cycles, then 0.3C / 0.3C, 0.5C / 0.5C, 1C / 1C to evaluate the rate performance of the battery, and finally 100 cycles at 1C / 1C to test the cycle performance of the battery.

[0075] The test results are shown in Table 1 below:

[0076]

[0077]

[0078] According to the test results in Table 1, the positive electrode material in each embodiment has better charge and discharge performance than that in the comparative example, has higher charge storage capacity and rate performance, and in each embodiment, the step-by-step temperature increase during the sintering process is beneficial to improving the initial charge and discharge efficiency of the battery. By comparing comparative example 3 and comparative example 4, it is proved that the addition of a sintering aid during the mixing process is helpful for the solid phase reaction during the low-temperature sintering of sodium ferric sulfate, and has better cycle performance and excellent long-cycle stability.

[0079] The positive electrode material of the present invention has high energy density, low cost, good stability, is environmentally friendly and has practical prospects.

[0080] contrast Figure 1 , Figure 2 and Figure 3 The present invention adopts the method of mixing sintering aid and surfactant to increase the uniformity of the mixed material, and the particle size of the sintered material is also reduced by comparison, and the large particles are significantly reduced. Compared with not adding a solvent, adding a solvent is conducive to the growth of crystals, and the crystal surface is smoother, which is conducive to exerting capacity.

[0081] The above content describes the technical principles, beneficial effects and features of the present invention. It should be pointed out that the above is only a preferred implementation mode of the present invention, but is not limited to the above embodiments. For technicians in the technical field to which the present invention belongs, some improvements and optimizations can be made without departing from the content of the present invention, which should be regarded as belonging to the protection scope of the present invention.

Claims

1. A method for preparing a sodium iron sulfate positive electrode material, characterized in that: The following steps are involved: (1) Weigh anhydrous ferrous sulfate, sodium source, carbon source and sintering aid; (2) Add oleic acid, and ball-mill in a ball mill under a nitrogen atmosphere according to a certain ball-to-material ratio. The milled slurry is dried in a vacuum drying oven; (3) The dried sample is subjected to a step-wise sintering treatment under a protective atmosphere to obtain a sodium iron sulfate positive electrode material.

2. The method for preparing a sodium iron sulfate positive electrode material according to claim 1, characterized in that: The sodium source in step (1) includes one or more of sodium sulfate, sodium bisulfate, sodium carbonate, sodium bicarbonate, sodium oxalate and sodium acetate.

3. The method for preparing a sodium iron sulfate positive electrode material according to claim 1, characterized in that: The carbon source in step (1) includes one or more of carbon nanotubes, ascorbic acid, citric acid, carbon black, graphite, nanographite, graphene and carbon fiber.

4. The method for preparing a sodium iron sulfate positive electrode material according to claim 1, characterized in that: The sintering aid in step (1) includes H3BO3, B2O3 or other boron-containing low-melting-point glass powder.

5. The method for preparing a sodium iron sulfate positive electrode material according to claim 1, characterized in that: The ball-to-material ratio in step (2) is 10-15:1, the ball milling speed is 300-600 r / min, and the ball milling time is 4-6 h.

6. The method for preparing a sodium iron sulfate positive electrode material according to claim 1, characterized in that: The temperature of the vacuum drying oven in step (2) is 80-100° C. and the drying time is 8-12 hours.

7. The method for preparing a sodium iron sulfate positive electrode material according to claim 1, characterized in that: The protective gas in step (3) is nitrogen or argon, the first step sintering temperature is 120-200°C, the holding time is 3-6h, the second step sintering temperature is 300-400°C, the heating rate is 2-5°C / min, and the holding time is 8-12h.

Citation Information

Cited By

  • Anion-doped sodium ferric sulfate positive electrode material for sodium ion battery as well as preparation method and application of anion-doped sodium ferric sulfate positive electrode material

    CN121097072A